Analysis of the International Experience in Providing Administrative Services to the Population: What Relevance for its Enforcement in Ukraine? - Ivanivna Zadoia, Ivanna; Denysyuk, Stanislav; Tanko, Andrii; Mikhailovich Nedrya, Kirill (DIXI, 2021)
It is a common interest and understanding that providing the population with administrative services is an important aspect for the proper functioning of every given society. There is no society without the proper management of its local population. It is to this end that there is a need to examine the position of international law in seeing the administrative management of its population with emphasis in the Ukrainian government. The objective of this article is: 1) to study international experience in providing administrative services; 2) to elaborate propositions for improving the processes related to the provision of administrative services to the population.The experience of foreign countries in the field of providing administrative services to the population (in particular, the United States, Canada and Western Europe) has been analyzed. It has been emphasized that Ukraine needs to build its own system of administrative services, taking into account effective models of carrying out public administration in developed Western countries. It has been noted that the quality of administrative services to the representatives of different segments of the population is one of those criteria, which assists in assessing the effectiveness of the entire state system of the country. It has been emphasized that the service state institution, whose activity is to provide both public and private administrative and legal services, the example of which can be the above-mentioned service institution of the Ministry of Internal Affairs, is only part of the large-scale reform of the existing state legal mechanism in Ukraine that has to change the essence of the functioning of state agencies in this area.
Keywords: provision of administrative services; public administration; public legal relations; transparent policy; administration area